2021
DOI: 10.1051/0004-6361/202140386
|View full text |Cite
|
Sign up to set email alerts
|

Cosmography by orthogonalized logarithmic polynomials

Abstract: Cosmography is a powerful tool for investigating the Universe kinematic and then for reconstructing the dynamics in a model-independent way. However, recent new measurements of supernovae Ia and quasars have populated the Hubble diagram up to high redshifts (z ∼ 7.5) and the application of the traditional cosmographic approach has become less straightforward due to the large redshifts implied. Here we investigate this issue through an expansion of the luminosity distance–redshift relation in terms of orthogona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 41 publications
1
34
0
2
Order By: Relevance
“…Risaliti & Lusso 2015. These expectations have already been confirmed in Bargiacchi et al (2021), where the same sample of QSOs (without the inclusion of BAO) is used for a cosmographic test of the flat ΛCDM model, with an improved estimation of the cosmographic free parameters, compared to the use of less updated QSO samples. It is worth mentioning some of the assumptions used in the cosmological analyses before moving on.…”
Section: Cosmological Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Risaliti & Lusso 2015. These expectations have already been confirmed in Bargiacchi et al (2021), where the same sample of QSOs (without the inclusion of BAO) is used for a cosmographic test of the flat ΛCDM model, with an improved estimation of the cosmographic free parameters, compared to the use of less updated QSO samples. It is worth mentioning some of the assumptions used in the cosmological analyses before moving on.…”
Section: Cosmological Resultsmentioning
confidence: 66%
“…Deviations from the spatially flat ΛCDM model would imply important theoretical and observational consequences and a change in our current understanding of cosmic evolution (e.g. Capozziello et al 2020), and are also observed at higher redshifts in the combined quasars (QSOs) and SNe Ia Hubble-Lemaître diagram, with a statistical significance of 3-4σ Lusso et al 2019Lusso et al , 2020Bargiacchi et al 2021). Such a joint analysis makes use of the observed non-linear relation between the ultraviolet and the X-ray luminosity in QSOs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…( 11), we first calculate the luminosity distance and then the distance modulus. In parallel way, one can use the logarithmic expansion of the luminosity distance in terms of redshift Bargiacchi et al 2019;Lusso et al 2019).…”
Section: Cosmographic Approach and Data Setsmentioning
confidence: 99%
“…Unlike the well-constraint from the 2015 quasar compilation, the 2020 quasar compilation gives a weak constraint on the dipole parameters. It appears that there is a tension at the 3σ -4σ confidence level between the cosmographic fit of the 2020 quasar compilation Hubble diagram and the one obtained by assuming a flat CDM model [57]. The difference between the 2015 and 2020 quasar compilation may due to the fact that the tension with the CDM model is not observed in the 2015 quasar compilation, which also seems to show a much higher dispersion in the Hubble diagram compared to the 2020 quasar compilation.…”
Section: Discussionmentioning
confidence: 81%